Model for training marathon swimmers in fins accounting for energy supply mechanism of muscle activity - Bakayev, V.; Bolotin, A. (Journal of Human Sport & Exercise, 2021)
Open-water marathon swimming with fins demands high levels of physical fitness from the athletes. The highest emphasis is placed on improving the general and speed endurance. This can only be achieved through targeted impact on the physiological structures of marathon swimmers, accounting for the individual characteristics of the mechanism behind the energy supply for muscle activity. Analysis of the literature has revealed that most works on training of marathon swimmers in fins do not provide sufficient data accounting for the individual specifics of the mechanism supplying energy for the athlete's muscle activity during training for competitions. This greatly limits the possibilities for differentiating the techniques and methods for improving general and speed endurance. Furthermore, methods for improving general and speed endurance in open-water marathon swimmers with fins, with different types of energy metabolism serving as the differentiation criterion, have not received sufficient attention. The existing system for training marathon swimmers in fins; for competitions does not offer satisfactory options accounting for the energy supply mechanism of muscle activity during practice. The system's main drawback is in the general approach to training of marathon swimmers in fins, which does not allow effectively increasing the general endurance and speeding endurance. Our findings indicate that the techniques and methods for training marathon swimmers in fins accounting for the individual characteristics of the mechanism for energy supply of muscular activity play a prominent role in improving the efficiency of training athletes for competitions. This actually helps athletes to achieve better results in training and in competitions. We have established that properly organized training sessions accounting for the individual characteristics of the energy supply mechanism of muscular activity have a higher efficiency. Studies have shown that the goals of developing general and speed endurance should be achieved in training marathon swimmers in fins in open water. General endurance is necessary for athletes to maintain high speed during the race, and speed endurance is necessary for building up speed at the finish. We have confirmed that special tasks during such training should be solved allowing for the individual characteristics of the mechanism for energy supply of muscular activity in marathon swimmers. The article reports on the results obtained for a training model developed for open-water marathon swimmers in fins, accounting for the individual peculiarities of the mechanism for energy supply to the athletes' muscular activity.